Socio-economic Status and Biological Characteristics of Students from Generation Z in France, Slovakia and Poland - Frąckiewicz, Ewa; Rębacz-Maron, Ewa; Czyżycki, Rafał; Pellat, Ghislaine; Marasová, Jana (Anthropological Review, 2025)
Generation Z, unlike any generation before them, lives in an era of rapid and global technological change, where most activities take place online. This lifestyle has significant implications for the well-being and health of internet users. The question is whether the contemporary socio-economic status (SES) and biological profile of Generation Z ‘immersed’ in new technologies is a universal phenomenon, independent of the country of residence. This study sets out to identify similarities and differences in the socio-economic and biological characteristics of Generation Z students from three European Union countries. Data were collected directly in France, Slovakia, and Poland. We used a survey questionnaire and non-invasive anthropometric measurements in Generation Z respondents (n=157). Our results show that there is a significant relationship between country of residence and three SES indicators: income, self-rated financial situation and time spent online, as well as three biological measures: body mass index (BMI), relative fat mass (RFM) and waist circumference (WC). Country of residence only partly explains the similarities and differences in the socio-economic status and biological characteristics of Generation Z students. In terms of SES, the participants’ profile is significantly influenced by financial situation, i.e. the student’s monthly disposable income and self-assessed financial situation, as well as time spent online. In turn, for biological factors, the significant measures are: BMI, RFM and WC.